2018
DOI: 10.1038/s41598-018-21268-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics provides novel insights into the mechanisms of selenium tolerance in the hyperaccumulator plant Cardamine hupingshanensis

Abstract: Selenium (Se) is an essential mineral element for animals and humans. Cardamine hupingshanensis (Brassicaceae), found in the Wuling mountain area of China, has been identified as a novel Se hyperaccumulator plant. However, the mechanism for selenium tolerance in Cardamine plants remains unknown. In this study, two cDNA libraries were constructed from seedlings of C. hupingshanensis treated with selenite. Approximately 100 million clean sequencing reads were de novo assembled into 48,989 unigenes, of which 39,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 80 publications
2
33
0
Order By: Relevance
“…The form of supplied Se may also have a significant effect on the response of a HA. A recent transcriptomic analysis of the Se HA Cardamine hupingshanensis found that, when supplied with selenite, the HA in fact downregulated the expression of its SULTR1;2 homolog ( Zhou et al, 2018 ). This result may be attributable to the fact that selenite is not likely to be transported through SULTRs, but rather through Pi transporters, due to the greater similarity of Pi to selenite ( White, 2018 ).…”
Section: Selenium Hyperaccumulatorsmentioning
confidence: 99%
“…The form of supplied Se may also have a significant effect on the response of a HA. A recent transcriptomic analysis of the Se HA Cardamine hupingshanensis found that, when supplied with selenite, the HA in fact downregulated the expression of its SULTR1;2 homolog ( Zhou et al, 2018 ). This result may be attributable to the fact that selenite is not likely to be transported through SULTRs, but rather through Pi transporters, due to the greater similarity of Pi to selenite ( White, 2018 ).…”
Section: Selenium Hyperaccumulatorsmentioning
confidence: 99%
“…All clean reads of Illumina RNA-seq corresponding to each pooled sample were mapped against the assembled reference transcriptome using bowtie 2 (V2.1.0). The FPMK (fragments per Kilobase Million) values of each isoform were computed for each pooled sample and normalized using the RPKM (RSEM 1.2.15) [59].…”
Section: Quantification Of Gene Expression Levelsmentioning
confidence: 99%
“…To date, studies on Se-tolerance mechanisms have focused on some Se-hyperaccumulating plants (Freeman et al, 2010; Sabbagh & Van Hoewyk, 2012; Cappa et al, 2015). In Cardamine hupingshanensis seedlings, the expression of the sulfite oxidase ( SOX ) gene in the roots is up-regulated after the addition of selenite, thus indicating that selenite may first be converted to selenate, and then the selenate is metabolized (Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%